Internalisasi Nilai-Nilai Tasawuf dalam Pembentukan Karakter Islami Generasi Muda di Era Modern: (Studi Analisis Tantangan Kontemporer) - Reyza Habib Fahrizky; Rais Hamsyah; Argi Sedyoyono; Hanif Saputra; Ismail Mubarok; Dede Nur Zaman (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
The rapid development of digital technology and globalization has significantly transformed the lifestyle of young generations. While these advancements provide numerous conveniences in accessing information and expanding knowledge, they also bring serious moral and spiritual challenges. Issues such as declining ethics, increasing materialism, individualism, and identity crises have become major concerns in contemporary society. In this context, Sufism (tasawuf) offers a relevant spiritual approach to strengthen Islamic character among youth. This study aims to analyze the internalization of Sufism values in shaping Islamic character in the modern era. The research employs a library research method by examining various academic sources related to Sufism, character education, and youth development. The findings indicate that Sufism values such as sincerity (ikhlas), patience (sabar), gratitude (syukur), humility (tawadhu’), ascetic awareness (zuhud), and spiritual consciousness (muraqabah) play a crucial role in forming strong Islamic character. The internalization of these values can be implemented through family education, formal institutions, religious organizations, and digital media. Therefore, Sufism functions not only as a spiritual practice but also as a foundational framework for developing morally grounded and spiritually resilient young generations in the modern era.